IS GENDER ISSUE STILL RELEVANT IN WORK ENGAGEMENT CONTEXT? (AN EVIDENCE IN BANKING SECTOR) - Adi, Agung Nugroho; Fithriana, Noora (The International Journal of Accounting and Business Society, 2021)
Research purposes- Gender issues was being relevant issue in the past decades. Also, work engagement play important roles to boost organization profitability. This paper aimed to investigate the differences between male and female employees in work engagement.Methodology- Sample for this study were 243 banking employees. Validity and reliability conducted in this study was using Confirmatory Factor Analysis (CFA) with the Work Engagement CFA score was .802 (sig.000) and Cronbach Alpha score for Work engagement was .900 (Minimum Score is 0.7) in SPSS 25. Independent T-test used in this research to find out the differences between male employees and female employees work engagement.Findings- The research Levene’s Test for F score was 1.820 (sig. 0179) or in other words is insignificant. So, the result conclusion was that it was not any differences in engagement significant level between female employees and male employees in the Indonesia banking sector.Practice Implication- To enhance productivity through work-engagement, banking industry has wide choice in recruiting female and male employee (both gender suitable with banking industry job description).Originality- Findings in this research occurred the relationship model between work-engagement based on gender perspectives.Keywords: Gender, Work Engagement, Productivity